Annotated checklist of eels (orders Anguilliformes and Saccopharyngiformes) from Taiwan - Ho, H.C.; Smith, D.G.; McCosker, J.E.; Hibino, Y.; Loh, K.H.; Tighe, K.A.; Shao, K.T. (2015)
An annotated checklist of eels, orders Anguilliformes and Saccopharyngiformes, occurring in Taiwanese waters is presented. The checklist is the result of a series of systematic studies conducted by the authors in the past few years. The eel fauna of Taiwan is one of the richest in the world with a total of 206 species in 74 genera and 13 families in Anguilliformes and a single species in Saccopharyngiformes. The most species-rich families are the Muraenidae with 71 species, followed by the Ophichthidae with 60 species, the Congridae with 29 species, and the Synaphobranchidae with 17 species. Moreover, three genera and 42 species have been described based on at least one type specimen collected from Taiwan. Of these, 36 species are recognized as valid and 23 species are known only from Taiwanese waters at present. Historical records of all Taiwanese eel species are reviewed by examining the original descriptions and figures, vouchers, as well as the recently collected specimens, where available. This represents the first detailed checklist of eels from Taiwanese waters.